International Spillovers of Forward Guidance Shocks - Jones, Callum (IMF Working Papers; Working Paper ;, 2018)
After 2007, countries that cut their policy interest rates close to zero turned, among other policies, to forward guidance. We estimate a two-country model of the U.S. and Canada to quantify how unexpected changes in U.S. forward guidance affected Canada. Expansionary U.S. forward guidance shocks, like conventional policy shocks, are beggar-thy-neighbor and depress Canadian output, but by twice as much as conventional shocks. We find that the effect of U.S. forward guidance shocks on Canadian output, unlike conventional policy shocks, depends on the state of U.S. demand and can be five times smaller when U.S. demand is weak.